A Bioinspired Gelatin–Amorphous Calcium Phosphate Coating on Titanium Implant for Bone Regeneration - Feng, Yanhuizhi; Wu, Di; Knaus, Jennifer; Keßler, Sascha; Ni, Bing; Chen, Zongkun; Avaro, Johnathan; Xiong, Rui; Cölfen, Helmut; Wang, Zuolin (My University, 2023)
Biocompatible and bio-active coatings can enhance and accelerate osseointegration via chemical binding onto substrates. Amorphous calcium phosphate (ACP) has been shown as a precursor to achieve mineralization in vertebrates and invertebrates under the control of biological macromolecules. This work presents a simple bioinspired Gelatin-CaPO4 (Gel-CaP) composite coating on titanium surfaces to improve osseointegration. The covalently bound Gel-CaP composite is characterized as an ACP-Gel compound via SEM, FT-IR, XRD, and HR-TEM. The amorphous compound coating exhibited a nanometer range thickness and improved elastic modulus, good wettability, and nanometric roughness. The amount of grafted carboxyl groups and theoretical thickness of the coatings are also investigated. More importantly, MC3T3 cells, an osteoblast cell line, show excellent cell proliferation and adhesion on the Gel-CaP coating. The level of osteogenic genes is considerably upregulated on Ti with Gel-CaP coatings compared to uncoated Ti, demonstrating that Gel-CaP coatings possess a unique osteogenic ability. To conclude, this work offers a new perspective on functional, bioactive titanium coatings, and Gel-CaP composites can be a low-cost and promising candidate in bone regeneration.
Keywords: 540